Evaluation of miR-21 and miR-375 as prognostic biomarkers in esophageal cancer. (21st October 2015) - Winther, Mette; Alsner, Jan; Tramm, Trine; Baeksgaard, Lene; Holtved, Eva; Nordsmark, Marianne
ABSTRACT: Background. MicroRNAs (miRNAs) have been associated with prognosis in esophageal cancer, suggesting a role for miRNAs to help guide treatment decisions. Especially, miR-21 and miR-375 have been investigated as prognostic biomarkers. The aim of this study was to evaluate the prognostic potential of miR-21 and miR-375 in primary esophageal squamous cell carcinomas (ESCC) and esophagogastric adenocarcinomas (EAC). Material and methods. Pre-therapeutic tumor specimens from 195 patients with loco-regional esophageal cancer treated with neoadjuvant or definitive chemoradiotherapy or perioperative chemotherapy were analyzed. Expression levels of miR-21 and miR-375 were quantified using Affymetrix GeneChip miRNA 1.0 Array. The Cox proportional hazards model was used to assess the correlation of miR-21 and miR-375 with disease-specific survival (DSS) and overall survival (OS). Forest plots were performed to evaluate the prognostic impact of miR-21 and miR-375 in the present study and previously published reports. Results. In ESCC, patients with miR-21 expression levels above median showed a trend towards poorer DSS and OS. When dividing miR-21 expression by tertiles, high levels of miR-21 significantly correlated with shortened DSS [HR 1.76 (95% CI 1.05–2.97) but not OS. Similarly for EAC, a significant association between miR-21 expression above median and DSS was observed [HR 3.37 (95% CI 1.41–8.05)], in addition to a trend towards poorer OS for patients with miR-21 expression above median. Multivariate analyses identified miR-21 as an independent prognostic marker for DSS in EAC [HR 3.52 (95% CI 1.06–11.69)]. High miR-375 was not correlated with improved prognosis in either histology. However, Forest plots demonstrated that both miR-21 and miR-375 were of prognostic impact in ESCC. Conclusion. In this study, miR-21 was identified as an independent prognostic biomarker for DSS in patients with EAC whereas miR-21 failed to show independent prognostic significance in ESCC. High miR-375 was not associated with enhanced survival in either histology.